Managing by zoning in the marine park islands in Mersing, Johor - Kassim, Zaleha; Ismail, Ahmad; Zakariya, Khalilah; Ahmad, Zuhairi; Abu Samah, Mohd Armi; Mohamed, Juliana; Yusof, Zeenat Begam; Shammodin, Muhammad Shaheed; Rosli, Nor Suhaila (2019)
The zonation of Marine Parks is known as a viable and an efficient management procedure in which different areas within the park are specified and limited for a certain function and activities. With the increase number of potential exploitation for fisheries and ecotourism industry, it is timely that more effort to be focussed to improve the management of the existing marine park islands as well as the nearby islands in the Mersing water. This study is aimed to propose the zonation of the Marine Park of Pulau Babi Besar, islands of Pulau Mertang and islands of Pulau Lima according to the classification of IUCN for Protected Area and zoning area as in the Great Barrier Reef Marine Park(GBRMP). Series of focus group discussions, interviews and field surveys were conducted in the islands and the mainland to collect sufficient data for the study area. All information on the valued environment and ecosystem biodiversity and development plans drafted by the Local Authority, State Government along with the guidelines from the Department of Town and Country Planning were analysed. Zone mapping were produced through a Global Information System and Remote Sensing technique for the study area.Considering the ‘Rancangan Kawasan Khas’ (RKK) for islands in Mersing 2018 which mainly focus on the strengtening the area as an ecotourism destination, several zonations were proposed for the study area following the Marine Park’s IUCN category. The Marine Park islands of Pulau Babi Besar are proposed to be zoned as 1a Strict Nature Reserve (all of the coastal area) and VI Protected Area with Sustainable Use of Natural Resources (selected areas).On the other hand, all islands in Pulau Mertang and Pulau Lima were proposed to be gazetted as the new Marine Park and zoned under 1a Strict Nature Reserve.